PERANCANGAN E-COMMERCE DALAM MENINGKATKAN PENGELOLAAN USAHA PENJUALAN - Suhartono, Joni; Made Karmawan, I Gusti (ISTEK WIDURI, 2020)
Over time, the development of technology in this digital era is growing very rapidly, so that our lives are made easier with the emergence of various kinds of applications. The problem in this research is that the company has difficulty in monitoring sales developments, the company has difficulty in developing markets to other areas, customers must come to the location to buy goods and pay cash. The purpose of this research is to design a web-based sales application for MSMEs. The method used in conducting the analysis is using SWOT while at the design stage using the waterfall method with UML tools. Applications designed to help MSMEs optimize their product sales activities, as well as make it easier for customers to place orders and payments and also increase and expand their business. The result of this research is that this UMKM e-commerce web application can help in monitoring orders, payments, and orders delivery.